Influência de um novo sistema de fotopolimerização na resistência adesiva dos cimentos resinosos em uma restauração inlay em zircônia de alta translucidez na região posterior - França, Carolina Gonzales (Universidade Estadual Paulista (Unesp), 2024)
Objective: To evaluate in vitro the influence of a new photopolymerization system to improve the polymerization effectiveness of resin cements used in the cementation of high translucency zirconia inlays in the posterior region, and consequently their mechanical properties. Material and Methods: Forty-eight third molars were prepared and randomly distributed into 2 control groups with indirect photoactivation and variation between dual and photoactivated resin cements and 2 groups with direct photoactivation with the use of fiber optics, also varying between dual and photoactivated resin cements. photoactivated. Alternative photopolymerization used a fiber optic device to improve polymerization effectiveness in difficult-to-access areas. For the analysis, the mechanical test was carried out using the microshear adhesive strength test and the results obtained were subjected to statistical analysis. Results: the direct photoactivation system with the fiber optic illuminator had statistical relevance (p<0.05) in improving adhesive strength in both groups and the dual cement was the one that achieved the highest adhesive strength among the cement group. Conclusion: The new device with illuminator is a promising alternative as it improved adhesive strength.

Objetivo: Avaliar in vitro a influência de um novo sistema de fotopolimerização para melhora da eficácia da polimerização dos cimentos resinosos utilizados na cimentação de inlays em zircônia de alta translucidez na região posterior, e consequentemente suas propriedades mecânicas. Material e Métodos: Quarenta e oito terceiros molares foram preparados e distribuídos aleatoriamente em 2 grupos controle com fotoativação indireta e variação entre os cimentos resinoso dual e fotoativado e 2 grupos com fotoativação direta com o uso da fibra óptica variando também entre os cimentos resinoso dual e fotoativado. A fotopolimerização alternativa utilizou um dispositivo de fibra óptica para melhora da efetividade da polimerização em áreas de difícil acesso. Para a análise, o ensaio mecânico foi realizado pelo teste de resistência adesiva por microcisalhamento e os resultados obtidos foram submetidos as análises estatísticas. Resultados: o sistema de fotoativação direta com o iluminador de fibra óptica teve relevância estatística (p<0.05) na melhora da resistência adesiva em ambos os grupos e o cimento dual foi o que obteve maior resistência adesiva entre o grupo cimento. Conclusão: O novo dispositivo com iluminador é uma alternativa promissora pois melhorou a resistência adesiva.
Influence of a new photopolymerization sistem on the adhesive strength of resin cements in a high translucency zircônia inlay restoration in the posterior region
Keywords: Cerâmica; Cimentos de resina; Luzes de cura dentária; Zircônia; Ceramics; Resin cements; Dental curing lights; Zirconia